CASPA (CArdiac Sarcoidosis in PApworth) improving the diagnosis of cardiac involvement in patients with pulmonary sarcoidosis: protocol for a prospective observational cohort study. Issue 1 (9th October 2020) - Quijano-Campos, Juan Carlos; Williams, Lynne; Agarwal, Sharad; Tweed, Katharine; Parker, Robert; Lalvani, Ajit; Chiu, Yi-Da; Dorey, Kane; Devine, Thomas; Stoneman, Victoria; Toshner, Mark; Thillai, Muhunthan
Abstract : Introduction: Sarcoidosis is a multisystem disease, predominantly affecting the lungs but can involve the heart, resulting in cardiac sarcoidosis (CS). Patients require MRI/Positron Emission Tomography (PET) scans for diagnosis. Echocardiography, ECG and Holter monitoring may be indicative but not diagnostic alone. Patients can present late with conduction defects, heart failure or sudden death. The CASPA (CArdiac Sarcoidosis in PApworth) study protocol aims to (1) use MRI to identify CS prevalence; (2) use speckle-tracking echocardiography, signal averaged ECG and Holter monitoring to look for diagnostic pathways; and (3) identify serum proteins which may be associated with CS. Methods and analysis: Participants with pulmonary sarcoidosis (and no known cardiac disease) from Royal Papworth Hospital will have the following: cardiac MRI with late gadolinium, two-dimensional transthoracic echocardiography with speckle tracking, signal averaged ECG and 24-hour Holter monitor. They will provide a serum sample for brain natriuretic peptide levels and proteomics by liquid chromatography coupled to high-resolution mass spectrometry. All data will be collected on OpenClinica platform and analysed approximately 6 months after final patient recruitment. Ethics and dissemination: The Camden & Kings Cross Research Ethics Committee approved the protocol (REC number: 17/LO/0667). Integrated Research Approval System (IRAS) 222 720. Dissemination of findings will be via conference presentations and submitted to peer-reviewed journals.